Regulatory Systems Strengthening for Medicines in Africa : Shining a Spotlight on the World Bank Group’s Decade-Long Contributions - World Bank (Washington, DC, 2022)
The African Medicines Regulatory Harmonization (AMRH) initiative, a multistakeholder partnership, focuses on improving fragmented regulatory systems in the region to ensure faster access to safe, efficacious, and good quality medicines and vaccines. With support from the Bill and Melinda Gates Foundation, the World Bank Group set up a trust fund in 2011 to support AMRH work. Since then, significant improvements have been made across the region, including notable decreases in timelines for the registration of medicines, more harmonized registration systems, and an enhanced focus on quality management and transparency in the drug registration process. The Coronavirus (COVID-19) pandemic has shown that harmonized and well-established regulatory systems are critical to ensure access to safe, efficacious, and good quality medicines and vaccines. The establishment of the African Medicines Agency, the next chapter in the AMRH initiative, provides the opportunity to continue institutionalizing this important medicine regulatory system’s strengthening work, while increasing country ownership and ensuring sustainability.